Women’s satisfaction with birth control methods - Khan, Laila; Ahmed , Manzoor; Gul, Tahira; Azeem, Umaira (International Journal of Endorsing Health Science Research, 2015)
The maternal and infant mortality in Pakistan is still high. The use of safe and important methods of contraception allows men and women to decide the number and spacing of their pregnancies and to improve the uptake and continuation of use of family planning services through improving the quality of family planning services. objectives of this study is to assess the quality of family planning services, asses information provided by providers to clients, asses client knowledge and satisfaction with services provided preferred choice and current method of contraception used by client. A cross sectional study was conducted from May to July 2014 in Family Planning Department of PIMS hospital, Islamabad by using consecutive sampling technique for data collection. Data was analyzed by using SPSS version 16. The information about each element of quality of care is present as a list of 25 indicators of quality of care each indicator specifies a percentage, mean or SD. Among 100 clients with 0.05 margin of error and 95% Confidence level (Zα/2). Majority of the clients were satisfied with the services of the facility. (40.27%) of the clients would like to have next child after >5 years while the mean age of the youngest child was 11.77 months with Standard deviation SD of 9.850. Majority of the clients (57%) choose Intra Uterine Contraceptive Device (IUCD) after consultation and 62.50% want to change their method. Non-availability of IEC material on FP was another problem. Rate of discontinuation is higher among women who have not been adequately counseled about side effects. It is concluded from this research study that the information provided to the clients were inadequate, this might be due to provider’s improper training and poor interpersonal communication and technical skills.